2021
DOI: 10.3389/fcvm.2021.678401
|View full text |Cite
|
Sign up to set email alerts
|

Elastogenesis Correlates With Pigment Production in Murine Aortic Valve Leaflets

Abstract: Objective: Aortic valve (AV) leaflets rely on a precise extracellular matrix (ECM) microarchitecture for appropriate biomechanical performance. The ECM structure is maintained by valvular interstitial cells (VICs), which reside within the leaflets. The presence of pigment produced by a melanocytic population of VICs in mice with dark coats has been generally regarded as a nuisance, as it interferes with histological analysis of the AV leaflets. However, our previous studies have shown that the presence of pigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…The addition of albino mice indicate that pigment production-rather than the presence of melanocytic populations-lead to the observed changes in elastic fiber patterning. We also found that elastic fibers in the WT leaflets were orthogonal to the collagen fibers, similar to the alignment known in human AoV (4,18). While not significantly different, we observed trends that indicate less orthogonality in the K5-Edn3 and Kit Wv elastic fibers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The addition of albino mice indicate that pigment production-rather than the presence of melanocytic populations-lead to the observed changes in elastic fiber patterning. We also found that elastic fibers in the WT leaflets were orthogonal to the collagen fibers, similar to the alignment known in human AoV (4,18). While not significantly different, we observed trends that indicate less orthogonality in the K5-Edn3 and Kit Wv elastic fibers.…”
Section: Discussionsupporting
confidence: 80%
“…The inner layers of VICs are responsible for producing and maintaining the ECM. The VICs comprise a heterogeneous population of cells that include smooth muscle cells, fibroblasts, myofibroblasts, neurons and glia (4,5). Besides these subpopulations of VICs, murine heart valves contain melanin producing cells, the melanocytes (6).…”
Section: Introductionmentioning
confidence: 99%
“…SYBR Green-based (Thermo Fisher Scientific# 4385612) quantitative real-time (RT) PCR was performed to calculate mean relative gene expression after normalization of C t values to glyceraldehyde 3-phosphate dehydrogenase ( GAPDH ) using the ΔΔ Ct method. GAPDH has previously been utilized as a control gene for normalization in aortic valve leaflets ( 40 ). All primer sequences are provided in Supplementary Data 2 .…”
Section: Methodsmentioning
confidence: 99%
“…116 Murine aortic valves contain pigment-producing melanocytes, 117 which are easily confused for positive von Kossa staining (which identifies calcium deposits) because both appear as brown precipitates. Melanocytes in VICs help to produce the elastin of the leaflet 118,119 ; whether a similar population exists in humans in unknown. Ovine, porcine, and bovine models better recapitulate the CAVD observed in humans, but large-animal models entail high cost and space requirements.…”
Section: Congenital Bicuspid and Unicuspid Valvesmentioning
confidence: 99%